Scientific Academic Writing Skills Among University Students: Results from a Self-Assessment Survey - Lussy Midani Rizki; Stevi Natalia; Nurafni; Suparman; Darhim Kusumah; Yaya S. Kusumah; Dadang Juandi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
This qualitative descriptive study provides a comprehensive profile of scientific academic writing skills among university students enrolled in mathematics education and primary school teacher education programs. Using a self-assessment survey, 110 students evaluated their proficiency across various dimensions of scientific writing, including clarity and coherence, organization of scientific arguments, use of scientific terminology, citation and referencing, critical evaluation of literature, and independent thinking. The data were analyzed using descriptive statistics to identify trends, strengths, and areas for improvement in students' writing skills. The findings revealed that students generally feel confident in their ability to construct clear academic paragraphs and use appropriate vocabulary and tone, but struggle with higher-order writing tasks such as synthesizing information from multiple sources and organizing extended scientific texts. Many students also expressed difficulties in applying proper citation and referencing styles, particularly APA format. Key strengths identified in the study include competence in basic grammar, punctuation, and paragraph structure, while notable weaknesses were found in areas such as critical evaluation, organizing complex arguments, and correct application of citation conventions. These results suggest a need for targeted instructional interventions to help students develop the advanced scientific writing skills necessary for academic success. The study's findings contribute to the ongoing discourse on improving scientific academic writing pedagogy, offering insights for educators to better support students in mastering these critical skills.